2019
DOI: 10.1039/c9cc01755k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-unsubstituted cycloalkylimines containing a 4 to 8-membered ring

Abstract: Primary cycloalkylimines with a 4 to 8-membered ring have been synthesized by dehydrocyanation of the corresponding α-aminonitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Guillemin et al reported carrying out the dehydrocyanation of aminonitriles to give imines by utilizing KOH in vacuo . 13 After the investigation, we found K 2 CO 3 to be an appropriate solid base for the present transformation of N -benzhydryl substrates. Thus, enantioenriched 2 was ground into a fine powder with K 2 CO 3 and the mixture was heated at 50 °C in vacuo .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Guillemin et al reported carrying out the dehydrocyanation of aminonitriles to give imines by utilizing KOH in vacuo . 13 After the investigation, we found K 2 CO 3 to be an appropriate solid base for the present transformation of N -benzhydryl substrates. Thus, enantioenriched 2 was ground into a fine powder with K 2 CO 3 and the mixture was heated at 50 °C in vacuo .…”
Section: Resultsmentioning
confidence: 79%
“…1 ). In the reverse reaction, dehydrocyanation 13 proceeded stereoselectively with the loss of a stereocenter to give the corresponding enantiomorphic crystals of achiral imines. Furthermore, the inversion of the enantiomorphic crystals of an achiral compound was observed for the first time; therefore, the (+)-crystal of the imine was transformed to its enantiomorphic (−)-crystal by carrying out HCN addition and then elimination and vice versa .…”
Section: Introductionmentioning
confidence: 99%
“…Oxirane-1-d. 2-Chloroethanol-1-d (1.63 g, 20 mmol) was then vaporised in a vacuum line (0.1 mbar) onto t-BuOK in powder heated to 90 o C (for similar experiments see Guillemin et al 2019). A trap cooled to −100 o C removed selectively the impurities (mainly t-butanol) and oxirane-1d was selectively condensed in a trap cooled at 77 K at a yield of 0.60 g or 67%.…”
Section: Synthesis Of Mono-deuterated Oxiranementioning
confidence: 99%
“…α-Aminonitriles have been synthesized in the mid-19th century by Adolph Strecker using a multicomponent reaction . Primary α-aminonitriles are well-known and well-studied compounds involved in numerous reactions, and precursors of various species such as amino acids by acid hydrolysis, amines via a Bruylants reaction or imines by basic dehydrocyanation. They probably played a key role on the Primitive Earth and the simplest derivative, aminoacetonitrile, has been detected in the interstellar medium . To our knowledge, the corresponding phosphorus and arsenic derivatives have not yet been synthesized, whereas numerous functionalized phosphines and arsines were synthesized shortly after the nitrogen derivatives, such as vinylamine, , vinylphosphine and vinylarsine .…”
Section: Introductionmentioning
confidence: 99%